Clinical features of symptomatic acquired lacrimal outflow obstruction in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Background: Acquired lacrimal outflow obstruction (ALOO) may be either symptomatic (i.e., manifested by specific symptoms) or asymptomatic.Purpose: To identify the clinical features of symptomatic acquired lacrimal outflow obstruction in patients with type 2 diabetes mellitus (DM2).Material and Methods: Medical records of 284 patients with symptomatic ALOO were retrospectively examined. Of these patients, 56 (19.7%) were found to have DM2, and constituted the study group, and 228 (80.3%) had no diabetes, and constituted the control group. Specific eye examination methods included measurements of punctum size and tear meniscus height, tear production tests (Schirmer, Jones and tear film breakup tests), nasolacrimal test, tear absorbing test, reflux tests, assessment of lacrimal system balance, lacrimal irrigation, and lacrimal canaliculi probing.Results: DM2 was found in 19.7 ± 2.4% of patients with symptomatic ALOO. We identified the clinical features of symptomatic ALOO in patients with type 2 DM. The incidence of bilateral dacryocystitis (46.4 ± 6.7%) was 1.6-fold higher; dacryocystitis (60.7 ± 6.5%) was 1.5-fold higher; punctual occlusion (30.3 ± 6.1%), 1.3-fold higher; bilateral punctual occlusion (7.1 ± 3.4%), 2.7-fold higher; membranous stenosis (9.8 ± 3.3%), twice higher; pinpoint stenosis (9.8 ± 3.3%), 1.9-fold higher; and blepharitis (71.4 ± 6.0%), 1.4-fold higher in the above patients than in patients with symptomatic ALOO in the absence of type 2 DM (р < 0.05).  In addition, patients with symptomatic ALOO combined with type 2 DM were at average 8.1 years younger than non-diabetic patients with ALOO (р < 0.05).Conclusion: DM2 was found in 19.7 ± 2.4% of patients with symptomatic ALOO. Clinical features of symptomatic ALOO were noted in patients with DM2.
Keywords: acquired lacrimal outflow obstruction; type 2 diabetes mellitus; dacryocystitis